The impact of eating disorders on glaucoma - Kawka, Jakub; Baranowska, Alicja; Baranowska, Katarzyna; Czyżewski, Filip; Filipek, Kinga; Muciek, Michał; Mrugała, Sebastian; Mrugała, Waldemar; Skierkowski, Bartosz; Zalewska, Natalia (Journal of Education, Health and Sport, 2024)
Glaucoma is a group of progressive neuropathies of the optic nerve leading to the destruction of retinal ganglion cells and their axons. It is the leading cause of irreversible blindness worldwide, affecting over 70 million people residing in various geographical regions. This disease ranks second among the causes of blindness in patients. Up to 40% of them lose their vision within the first year of diagnosis.(1) The most common type of glaucoma affecting ophthalmic patients is open-angle glaucoma, in which the iridocorneal angle is not pathologically altered, but there is an elevation of intraocular pressure due to abnormal fluid flow within the eye. The main cause of this disease is obstruction of aqueous humor outflow from the eye and its excessive production. Although the exact mechanism of glaucoma is not fully understood yet, several risk factors have been identified, including high intraocular pressure (IOP), age, and genetics. Materials and Methods: Review and summary of research studies available in open-source format on Google Scholar, PubMed. Conclusions: There is ample evidence confirming the impact of food products on the risk of developing glaucoma or exacerbating its symptoms. However, further research is necessary to determine the extent of their interference with this disease entity.